Progress Report to the International Monetary and Financial Committee on the Activities of the Independent Evaluation Office of the IMF. (Policy Papers; Policy Paper ;, 2017)
This report describes recent follow-up on past Independent Evaluation Office (IEO) evaluations, summarizes the update of the 2006 evaluation of multilateral surveillance, and outlines the ongoing evaluations. It raises the concern that progress in implementing Board-endorsed IEO recommendations has been quite mixed, suggesting the need for further consideration to reinforcing the follow-up process.